2019
DOI: 10.1039/c9cp06019g
|View full text |Cite
|
Sign up to set email alerts
|

Band alignment and optical features in Janus-MoSeTe/X(OH)2 (X = Ca, Mg) van der Waals heterostructures

Abstract: van der Waals heterostructures can be effectively used to enhance the electronic and optical properties and extend the application range of two-dimensional materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(12 citation statements)
references
References 73 publications
0
12
0
Order By: Relevance
“…5c). Previous studies [40,[42][43][44][45] on other 2D honeycomb materials have proven that the band gap calculated by DFT obeys similar strain-dependency, suggesting that the electronic properties can be effectively regulated by changing strain, and g-C 3 N 4 is so flexible that may have potential applications in flexible devices. In addition, we have also calculated the PBE high transition probabilities between the upper most valence band (VB) and the lowest conduction band (CB) of g-C 3 N 4 , which are shown by the squares of the dipole transition matrix elements [46], P 2 , at k points in Fig.…”
Section: Electronic Propertiesmentioning
confidence: 78%
See 2 more Smart Citations
“…5c). Previous studies [40,[42][43][44][45] on other 2D honeycomb materials have proven that the band gap calculated by DFT obeys similar strain-dependency, suggesting that the electronic properties can be effectively regulated by changing strain, and g-C 3 N 4 is so flexible that may have potential applications in flexible devices. In addition, we have also calculated the PBE high transition probabilities between the upper most valence band (VB) and the lowest conduction band (CB) of g-C 3 N 4 , which are shown by the squares of the dipole transition matrix elements [46], P 2 , at k points in Fig.…”
Section: Electronic Propertiesmentioning
confidence: 78%
“…This is because HSE06 corrects the underestimation of band gap by partially removing the self interaction. Previous studies have shown that the hybrid-functional HSE06 method shows significant improvement of band gap of 2D materials [40][41][42][43]. Moreover, both PBE and HSE06 methods have shown the same variation trends of gap-strain curves.…”
Section: Electronic Propertiesmentioning
confidence: 81%
See 1 more Smart Citation
“…4 The successful synthesis of Janus MoSSe opened a new chapter in the research for the 2D family and many different types of Janus structures were theoretically studied recently. [6][7][8][9] Janus structures show a high prospect for use as thermoelectric materials due to their owning a high thermoelectric gure of merit. 10 With suitable band edge alignment, Janus structures are expected to be used in photocatalytic water splitting.…”
Section: Introductionmentioning
confidence: 99%
“…15 Recently, van der Waals heterostructures based Janus monolayers have been studied with a lot of attention. 7,16,17 In graphene/Ga 2 SSe heterostructures, a small band gap has been found in graphene due to weak interactions between graphene and Ga 2 SSe. 17 It implies that forming heterostructures with the Janus structure is one of the ways to overcome the gapless disadvantage of graphene.…”
Section: Introductionmentioning
confidence: 99%